2017
DOI: 10.1186/s12877-017-0686-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and control of hypertension among a Community of Elderly Population in Changning District of shanghai: a cross-sectional study

Abstract: AbstractsBackgroundHypertension is considered a major public health challenge. It is the most important risk factor for cardiovascular disease and is a prominent risk for China’s elderly population. However, few studies have addressed the effect of blood pressure control on elderly hypertension patients in China. In response, this study aimed to investigate the prevalence and control of hypertension in the elderly population in Shanghai’s communities.MethodsA secondary data analysis based on a government-finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 35 publications
(37 reference statements)
2
17
1
7
Order By: Relevance
“…There are five factors related to the self-efficacy of elderly people with systolic hypertension, including education, occupation before entering institutional rehabilitation, spiritual ac- tivities, length of stay, and dementia. In this study, education is related to the self-efficacy of the elderly people with systolic hypertension, which is consistent with previous studies indicating that lower education is linked with uncontrolled hypertension among elderly people (Yang et al, 2017). These results suggest that education contributes to the understanding of health information and the health literacy of the elderly.…”
Section: Factors Related To the Self-efficacy Of Elderly People With supporting
confidence: 92%
See 2 more Smart Citations
“…There are five factors related to the self-efficacy of elderly people with systolic hypertension, including education, occupation before entering institutional rehabilitation, spiritual ac- tivities, length of stay, and dementia. In this study, education is related to the self-efficacy of the elderly people with systolic hypertension, which is consistent with previous studies indicating that lower education is linked with uncontrolled hypertension among elderly people (Yang et al, 2017). These results suggest that education contributes to the understanding of health information and the health literacy of the elderly.…”
Section: Factors Related To the Self-efficacy Of Elderly People With supporting
confidence: 92%
“…The current study found that the prevalence of systolic and diastolic hypertension among the elderly is low compared to the hypertension of elderly people in Shanghai (Yang et al, 2017), although the prevalence of elders with hypertension is higher than in the Indonesian basic health survey (Badan Penelitian dan Pengembangan Kesehatan, 2013). The difference in hypertensive outcomes among the elderly people may be due to differences in the setting of the study site and the character-istics of the elderly people.…”
Section: Prevalence Of Hypertension Among the Elderly In Institution-contrasting
confidence: 49%
See 1 more Smart Citation
“…), especially among an older adult population and men (World Health Organization ; Yang et al. ). Among those, over 1 billion experience uncontrolled hypertension (Rouf et al.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, it is estimated that 7.5 million people with hypertension die every year as hypertension is a leading risk factor for cardiovascular disease (WHO 2018;Wr a ak et al 2015). Worldwide, the prevalence of hypertension is more than 1.1 billion which rises from 594 million (Forouzanfar et al 2017), especially among an older adult population and men (World Health Organization 2018;Yang et al 2017). Among those, over 1 billion experience uncontrolled hypertension (Rouf et al 2018;World Health Organization 2018;Zhou et al 2018).…”
Section: Introductionmentioning
confidence: 99%